Los olvidados de Buñuel: recepción, literacia fílmica e identidad nacional - Novoa Fernández, Olivia (2017)
In 2003 the origina/ film negativa of Los Olvidados was enlistcd at the UNESCO's Memory of the World Programme; which aims to preserve the most representative cultural heritage of languages, people and cultures in the worfd- The film premiere took place on November W', 1950 at Cine Mexico. A week laier, it was withdrawn because it portrayed an inconvenient and annoying representation ofthe country. Ijnlike Buñuel's earlier works, provoking the spectator's cyc with surrealistic, erotic and violent images, in Los Olvidados, the fi/mmaker assailed the audience in two fronts: on the one hand, the spectator's eye, who is unfamiliar with the cruelty of realify and, in a Mexican context, their national identity- I intend to highlight the fact that the film 's initial refusal in Mexico is intrinsically related to the construction of Mexican national identity, carried out through film pedagogy sponsored by the state and based on the paradigm of melodrama From a film literacy perspective, / propose to analyse this film, which was refused, criticized, accepted and applauded. Therefore, al/ these vicissitudes resulted not on/y from the subversion of film language in Buñuel's works but also from the actual context and cultura/ representations constructed at that time.